Comparison of PED and FRED flow diverters for posterior circulation aneurysms: a propensity score matched cohort study - Griessenauer, Christoph J.; Ulfert, Christian; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2021)
Background Flow diversion is a common endovascular treatment for cerebral aneurysms, but studies comparing different types of flow diverters are scarce. - Objective To perform a propensity score matched cohort study comparing the Pipeline Embolization Device (PED) and Flow Redirection Intraluminal Device (FRED) for posterior circulation aneurysms. - Methods Consecutive aneurysms of the posterior circulation treated at 25 neurovascular centers with either PED or FRED were collected. Propensity score matching was used to control for age, duration of follow-up imaging, adjunctive coiling, and aneurysm location, size, and morphology; previously ruptured aneurysms were excluded. The two devices were compared for the following outcomes: procedural complications, aneurysm occlusion, and functional outcome. - Results A total of 375 aneurysms of the posterior circulation were treated in 369 patients. The PED was used in 285 (77.2%) and FRED in 84 (22.8%) procedures. Aneurysms treated with the PED were more commonly fusiform and larger than those treated with FRED. To account for these important differences, propensity score matching was performed resulting in 33 PED and FRED unruptured aneurysm pairs. No differences were found in occlusion status and neurologic thromboembolic or hemorrhagic complications between the two devices. The proportion of patients with favorable functional outcome was higher with FRED (100% vs 87.9%, p=0.04). - Conclusion Comparative analysis of PED and FRED for the treatment of unruptured posterior circulation aneurysms did not identify significant differences in aneurysm occlusion or neurologic complications. Variations in functional outcomes warrant additional investigations.
Published Online First 1 July 2020
Gesehen am 13.04.2021